Insulin secretion and insulin sensitivity in diabetic and non-diabetic subjects with hepatic nuclear factor-1alpha (maturity-onset diabetes of the young-3) mutations - Vaxillaire, M; Pueyo, ME; Clement, K; Fiet, J; Timsit, J; Philippe, J; Robert, JJ; Tappy, L; Froguel, P; Velho, G (European journal of endocrinology, 1999)
OBJECTIVE: To evaluate insulin secretion and sensitivity in affected (diabetes mellitus or impaired glucose tolerance; n=7) and in unaffected (normal glucose tolerance; n=3) carriers of hepatocyte nuclear factor-1alpha (maturity-onset diabetes of the young-3 (MODY3)) gene mutations. METHODS: Insulin secretion was assessed by an i.v. glucose tolerance test (IVGTT), hyperglycemic clamp and arginine test, and insulin sensitivity by an euglycemic hyperinsulinemic clamp. Results were compared with those of diabetic MODY2 (glucokinase-deficient) and control subjects. RESULTS: The amount of insulin secreted during an IVGTT was decreased in affected MODY3 subjects (46+/-24 (s.d.) pmol/kg body weight (BW)) as compared with values in MODY2 (120+/-49pmol/kg BW) and control (173+/-37pmol/kg BW; P=0.0004) subjects. The amount of insulin secreted during a 10mmol/l glucose clamp was decreased in affected MODY3 subjects (171+/-78pmol/kg BW) and MODY2 subjects (302+/-104pmol/kg BW) as compared with control subjects (770+/-199pmol/kg BW; P=0.0001). Insulin secretion in response to arginine was decreased in affected MODY3 subjects. Milder and heterogeneous defects were observed in the unaffected MODY3 subjects; the amount of insulin secreted during the hyperglycemic clamp was 40-79% of that of controls. The response to arginine was abnormally delayed. Insulin sensitivity was decreased in diabetic but not in non-diabetic MODY3 subjects. CONCLUSIONS: Beta-cell dysfunction in response to glucose and arginine is observed in affected and unaffected MODY3 subjects. The MODY3 and MODY2 subtypes present different insulin secretion profiles. Secondary insulin resistance might contribute to the chronic hyperglycemia of MODY3 patients and modulate their glucose tolerance.